Yemelyanova O. V. Modality of the discourse of financial prediction - Yemelyanova O.V. (Philological Treatises, 2020)
The article deals with the analysis of the category of modality in the discourse of financial prediction. It has been found that the mood is the main linguistic representation of objective modality. Linguistic means of subjective modality representation in the discourse of financial prediction are modal verbs, which are connected directly with the author’s intention, modal words, adverbs.